Du Mont Liban aux sierras d'Espagne : sols, eau et sociétés en Montagne : autour du projet Franco-Libanais CEDRE "Nahr Ibrahim" - Harfouche, Romana,; Poupet, Pierre, (Archaeopress Publishing Ltd, 2015)
This volume presents the results of the CEDRE multidisciplinary project 'Nahr Ibrahim' that was led on the Lebanese mountain centred around the Nahr Ibrahim valley (the famous Adonis valley in antiquity), in the hinterland of the ancient city of Byblos. The history of settlement patterns and the construction of agricultural mountainous landscapes since the Early Bronze Age is examined, with comparisons from other regions surrounding the Mediterranean basin.